The HA-incorporated nanostructure of a peptide–drug amphiphile for targeted anticancer drug delivery. Issue 32 (1st April 2016) - Choi, Huyeon; Jeena, M. T.; Palanikumar, L.; Jeong, Yoojeong; Park, Sooham; Lee, Eunji; Ryu, Ja-Hyoung
Abstract : We demonstrate targeted anticancer drug delivery using transformable nanostructures of the complex of hyaluronic acid (HA) and KCK–CPT, a prodrug amphiphile composed of camptothecin (CPT) and tripeptide (KCK). Abstract : A simple peptide based prodrug of camptothecin (CPT) has been synthesised in which the CPT is conjugated to a tripeptide (KCK) via a disulfide linkage (KCK–CPT) and self-assembled into well-defined nanostructures in water depending on the concentration. The hyaluronic acid (HA) complex of KCK–CPT exhibited target specific toxicity with excellent antitumour efficiency.